2022
DOI: 10.3389/fphy.2022.988407
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and solutal energy transport analysis in entropy generation of hybrid nanofluid flow over a vertically rotating cylinder

Abstract: An investigation of an axisymmetric mixed convective boundary layer flow of silver-titanium dioxide/water (Ag−TiO2/H2O) hybrid nanofluid towards vertically and rotating stretching cylinder with entropy generation is conducted. The Cattaneo-Christov theory and joule heating effect are used to analyze the features of thermal energy. Moreover, the magnetic impact and convective boundary conditions on the vertical surface also considered in the current investigation. The developing equations for momentum, energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It can be concluded that the presence of entropy generation affects the fluid flow of a hybrid nanofluid, which can be a control parameter for a certain process. The details of the discovery of the entropy generation can be seen in previous studies [94][95][96][97][98][99][100][101][102][103][104].…”
Section: Entropy Generation Of a Hybrid Nanofluidmentioning
confidence: 99%

Exploration of Recent Developments of Hybrid Nanofluids

Nur Syahidah Nordin,
Abdul Rahman Mohd Kasim,
Masyfu’ah Mokhtar
et al. 2024
ARFMTS
“…It can be concluded that the presence of entropy generation affects the fluid flow of a hybrid nanofluid, which can be a control parameter for a certain process. The details of the discovery of the entropy generation can be seen in previous studies [94][95][96][97][98][99][100][101][102][103][104].…”
Section: Entropy Generation Of a Hybrid Nanofluidmentioning
confidence: 99%

Exploration of Recent Developments of Hybrid Nanofluids

Nur Syahidah Nordin,
Abdul Rahman Mohd Kasim,
Masyfu’ah Mokhtar
et al. 2024
ARFMTS